The Effect of the Problem-Based Learning Model with Interactive Media on the Economics Learning Outcomes of Class X Students of SMA Negeri 7 Medan - Rio Ricardo Damanik; Putri Kemala Dewi Lubis (Jurnal Ilmiah Pendidikan Holistik (JIPH), 2023)
The problem in this study is the less than optimal learning outcomes in economics class X Social Sciences SMA Negeri 7 Medan. The purpose of this research is to find out: The effect of Problem Based Learning Learning Model with Interactive Media is higher than Problem Based Learning Model. The population in this study were all students of class X IPS SMA Negeri 2 totaling 140 students while the sample in the study was 70 students consisting of 2 classes using purpose sampling. This study used several tests, namely Test Instrument Tests in the form of Test Validity tests, Test reliability tests, Analysis of Difficulty Levels and analysis of discriminating power. After the test instrument test is used test prerequisite analysis in the form of normality test and homogeneity test. The findings in this study indicate that the average value of post-test learning outcomes for the experimental class using the Problem Based Learning learning model with interactive media is 80.20 and the control class using the Problem Based Learning learning model is 71.11 where it can be concluded that the effect of the Problem Based Learning Model is with Interactive Media is higher than the Problem Based Learning model on learning outcomes in economics class X social studies at SMA Negeri 7 Medan T.P 2022/2023.